International price dispersion and market segmentation in Japan and the United States: Theory and empirics - Kwok-Chiu Fung; Alicia Garcia-Herrero; Francis Ng (Asian Development Bank Institute (ADBI), 2013)
This paper focuses on the pricing behavior of Japanese and United States firms selling their identical products in New York City, Chicago, Osaka, and Tokyo. The authors utilize some simple models of international price dispersion and market segmentation that generate predictions about testable prices. The dataset, which consists of prices of identical products in the Japanese and American cities, was collected and accepted by both governments. Using this data, versions of international price dispersion theories are tested and some empirical evidence to support the view that simple international price dispersion models can partly explain the observed prices is found.
Keywords: F12; F14; L11; L13; 330; pricing behavior; price dispersion; price dispersion theories; international price dispersion; Preismanagement; Multinationales Unternehmen; Preisspanne; Internationale Marktsegmentierung; New York (NY); Chicago (Ill.); Osaka; Tokio